2003
DOI: 10.1016/s0896-6273(03)00164-8
|View full text |Cite
|
Sign up to set email alerts
|

Circadian Dynamics of Cytosolic and Nuclear Ca2+ in Single Suprachiasmatic Nucleus Neurons

Abstract: Intracellular free Ca(2+) regulates diverse cellular processes, including membrane potential, neurotransmitter release, and gene expression. To examine the cellular mechanisms underlying the generation of circadian rhythms, nucleus-targeted and untargeted cDNAs encoding a Ca(2+)-sensitive fluorescent protein (cameleon) were transfected into organotypic cultures of mouse suprachiasmatic nucleus (SCN), the primary circadian pacemaker. Circadian rhythms in cytosolic but not nuclear Ca(2+) concentration were obser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

21
271
4

Year Published

2004
2004
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 250 publications
(296 citation statements)
references
References 54 publications
21
271
4
Order By: Relevance
“…In a previous study, Ikeda et al (2003) demonstrated a TTXresistant circadian rhythm in cytosolic, but not nuclear, Ca 2ϩ concentration. These data are not necessarily at variance with our findings.…”
Section: Discussionmentioning
confidence: 75%
“…In a previous study, Ikeda et al (2003) demonstrated a TTXresistant circadian rhythm in cytosolic, but not nuclear, Ca 2ϩ concentration. These data are not necessarily at variance with our findings.…”
Section: Discussionmentioning
confidence: 75%
“…1), nuclear GECIs can be generated by attaching nuclear localization sequences to cytosolic GECIs. Actually, a variety of fluorescent indicators including FRET-type and single-FP-type GECIs have been used to visualize nuclear Ca 2þ signals, showing that the nuclear Ca 2þ signal is mostly synchronized with the cytosolic Ca 2þ signal (9,16,19,21,(54)(55)(56)(57).…”
Section: Nucleusmentioning
confidence: 99%
“…In mammals, there is increasing evidence that voltage-dependent calcium channels (VDCCs) may contribute to the clock function of SCN cells. SCN neurons exhibit the following: circadian rhythms of intracellular calcium concentration (Colwell, 2000;Ikeda et al, 2003), all major subtypes of VDCC currents (Cloues and Sather, 2003), and oscillations in the calcium currents generated by some VDCC subtypes (Pennartz et al, 2002;Kim et al, 2005). VDCCs have also been implicated in SCN intercellular communication, because treatment with cadmium, a nonselective calcium channel antagonist (Cloues and Sather, 2003), disrupts the synchronization of circadian rhythms in firing rate be-tween synaptically paired SCN neurons (Shirakawa et al, 2000).…”
Section: Introductionmentioning
confidence: 99%